Pretreatment with Shuanghe-Tang Extract Attenuates Postischemic Brain Injury and Edema in a Mouse Model of Stroke: An Analysis of Medicinal Herbs Listed in Dongui Bogam. (11th February 2018) - Kim, Min Jae; Lee, Seo-Yeon; Hwang, Ji Young; Kim, Hyunha; Ha, Ki-Tae; Choi, Byung Tae; Baek, Jin Ung; Shin, Hwa Kyoung
Abstract : Aim . Although stroke is among the leading causes of death and long-term disability, there are few effective treatments for limiting the severity of neurological sequelae. We evaluated the effects of 29 medicinal herbs listed in the Pung chapter of the 17th century Korean medical text Dongui Bogam on stroke symptoms in a mouse model of cerebral ischemia. Methods . Focal cerebral ischemia was induced via photothrombosis. Infarct volume, brain edema, and neurological deficits were evaluated. Immunofluorescence staining for tight junction proteins and aquaporin 4 (AQP4) was performed following ischemic injury. Results . Based on our initial findings, we examined the effects of two prescriptions in which the candidate herbs comprised more than 60% of the total formula: Shuanghe-tang and Zengsunsiwu-tang. Pretreatment with Shuanghe-tang significantly reduced infarct volume, decreased blood-brain barrier (BBB) breakdown, attenuated edema, and improved neurological and motor functions in a dose-dependent manner (30, 100, and 300 mg/kg), while no such effects were observed in mice pretreated with Zengsunsiwu-tang. Immunohistochemical analysis revealed significant increases in ipsilateral occludin and zonula occludens 1 (ZO-1) expression in Shuanghe-tang-pretreated mice, as well as increased AQP4 immunofluorescence. Conclusions . These results indicate that Shuanghe-tang may protect against brain injury and promote recovery of neurological function following ischemia.